RFID Tag-equipped Drone for Antenna Array-based Localization: A Step-by-Step MATLAB Simulation Tutorial - Arif Abdul Aziz; Muhammad Miftahul Amri (Engineering Science Letter, 2022)
In the last decades, Radio Frequency Identifiers (RFID) has gained massive popularity.In the last decades, Radio Frequency Identifiers (RFID) have gained massive popularity. RFID technology allows data to be encoded in a small form (tag). The data contained inside the RFID tag can be captured wirelessly by the RFID reader through electromagnetic (EM) waves. On the other hand, localization techniques have achieved significant developments in the last decade. There is a wide range of localization tool variations, including satellite-based localization (i.e., GPSS, GLONASS), Bluetooth Low Energy (BLE), IMU, camera, infrared sensor, and even RF-based localization. In this work, we present an accurate localization technique via battery-less passive RFID tag-UAV integration. We have employed two low-complexity methods: generalized cross-correlation with phase transformation (GCC-PHAT) algorithm and triangulation technique. By simulation, we have validated that an accurate antenna array-based dynamic localization can be realized. For the sake of simplicity, we only demonstrate two-dimensional movement. However, the identical method can also be used in the three-dimensional movement. While this paper considers only two antenna arrays and one RFID tag, the proposed concept can be expanded to a more extensive system with a larger number of antenna arrays and RFID tags.